An analysis of new English words created during COVID-19 - Nabila, Ersyalia; Abdulrahman, Tryanti R. (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
The COVID-19 pandemic affects almost all aspects of life, including social and language aspects. One of the phenomena of language change is the emerging of new words during COVID-19. Taken from a linguistic perspective, this research aims to analyze the new words created during COVID-19, to analyze their meaning of the new words, and how they affect human social life. The method used in this research is discourse analysis using a descriptive qualitative research design. The researchers collected these new English words from social media, books, articles, and news. Findings reveal that there are nineteen new English words created during COVID-19. These new words are now very popular on social media and are used in general conversation. In addition, it suggests that these new words have profoundly affected our social life and also the teaching and learning process of English.